Improving Volunteers' Teaching Skills Through an Internship Program at the Bandar Klippah Dakwah Spring Quran House - Ifrohul Fadhilah; Ahmad Roihan; Imam Kurniawan Nasution; Arrahman Aji Prabowo; Daffa Haikal; Wan Alif Ihza Mahendra; Abdul Halim (ENGAGEMENT: Jurnal Pengabdian Masyarakat, 2025)
This study aims to improve the teaching skills of volunteers through an internship program at the Dakwah Spring Al-Quran House in Bandar Klippah. The research was motivated by the need for competent and dedicated teachers to support the Quranic learning process in the community. A qualitative approach was used, utilizing observation, interviews, and documentation of volunteers participating in the internship program. The results showed that the internship program provided volunteers with hands-on experience in classroom management, developing teaching materials, and implementing effective learning methods. Furthermore, volunteers received regular guidance and evaluations from experienced mentors, improving their pedagogical skills and teaching confidence. Another positive impact was the formation of a solidarity network among volunteers, strengthening their motivation and commitment to preaching. The study concluded that the internship program at the Dakwah Spring Al-Quran House in Bandar Klippah was effective in improving volunteers' teaching skills and could serve as a model for human resource development in other Quranic educational institutions. It is recommended that this internship program be continuously developed and periodically evaluated for optimal results.